Debt, equity, universal banking and Islamic finance: A note - HASAN, Zubair (Journal of Economic and Social Thought, 2018)
Abstract. This brief note looks at the suggested use of universal banking as a tool to mitigating risk in financing operations’ arising at both ends of the market – demand and supply. It concludes that the issue of adopting universal banking in the Islamic system is of little significance for risk reduction. It essentially raises the issue of mega banks versus smaller units in the Islamic system where the discretion would opt for the latter. Keywords. Equity versus debt financing, Universal banking, Islamic finance. JEL. D10, D11, E20.